Gambaran Adiksi Penggunaan Instagram pada Remaja SMA di Jakarta Selatan - Prahastia Kurnia Putri; Fatma Nuraqmarina; Cita Utami (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2022)
Aim of this study is to know the descriptions of Instagram addiction among senior high school students in Jakarta. Adolescence is a phase with better physical and socialization with peers, they have to fullfill their belongingness and love needs with various methods, one of them is social media named Instagram. Instagram is most known and used social media compared to others, so this is possible if users open Instagram frequently or, addicted to Instagram. This study uses theory from Andreassen et al (2015) about Social Media Addiction that was referred from DSM 5 Internet Addiction Disorder criterion, there are 6 aspects of media social addiction: Salience, Mood Modification, Tolerance, Withdrawal, Conflict, and Relapse. Instrument of this study uses adaptation of Bergen Social Media Addiction Scale (BSMAS), with incidental sampling to 265 High Schools students in Jakarta Selatan and analyzed uses descriptive statistics.  Findings of this research shows  that there is no significant differences between boys and girls in Instagram addiction, eventhough girls have slightly higher mean to boys. Besides, Tolerance is the highest aspect of Addiction and the lowest is Conflict.